Integrating digital skills into English language teaching: Implications for teacher performance - Rodriguez-Barboza, Jhonny Richard; Carreño-Flores, Oscar David; Mendoza-Zuñiga, Marleni; Michca-Maguiña, Mary Hellen Mariela (Revista de Ciencias Sociales, 2025)
Research underscores the importance of enhancing teachers’ digital competencies to effectively address contemporary educational challenges and improve educational quality. Therefore, this study aimed to examine the impact of digital skills on the teaching performance of English teachers at a private university in Lima, Peru. Adopting a quantitative approach with a non-experimental and correlational design, the study conducted surveys with 85 teachers. The results indicate a significant relationship between digital skills and overall teaching performance, explaining 71.4% of the variability. However, the study did not find a significant impact of digital skills on specific dimensions of teaching performance, such as disciplinary proficiency, didactic aspects, didactic thinking, motivation, and self-efficacy. This suggests that other factors, such as academic background and professional experience, may have a greater influence in these areas. Finally, the study highlighted the need for universities to prioritize the development of digital skills among educators, while recognizing the continued importance of traditional academic and professional factors in teaching effectiveness.